Self-assembly of defect-rich graphene oxide nanosheets with Na2Ti3O7 nanowires and their superior absorptive capacity to toxic dyes. (23rd May 2017) - Sun, Yibai; Fu, Wanlin; Dai, Yunqian; Huang, Yiyang; Zhou, Jie; Huang, Chengqian; Yang, Chongya; Huang, Meiyou; Ma, Rongwei; Lin, Baoping
Abstract: Graphene sheets, a flexible 2D material with excellent absorptive capacity, have great potential as absorbing materials. However, this material has always suffered from irreversible aggregation and thus loses the abundant active sites and large surface area. In this paper, large-scale graphene oxide (GO) sheets were cut and reduced to tiny reduced graphene oxide (RGO) sheets by a cell-break sonicator, for producing numerous defects, which are the center of chemisorption. Furthermore, sodium titanate nanowires functioned as a framework to help to disperse the tiny RGO sheets uniformly. And, in turn, the flexible tiny RGO sheets glued robust nanowires into a free-standing membrane. This novel composite membrane exhibited an ultra-high decoloration efficiency of 99.8% of rhodamine B in a continuous flow mode, and an outstanding absorptive capability of 1.30 × 10 −2 mol g −1 correlated to RGO content in batch reaction, which is about two orders of magnitude higher than other reported graphene-based absorbents. In addition, an efficient and feasible method without any heat treatment for regenerating the membrane is illustrated, and the recycled membrane retains superior decoloration efficiency. The excellent absorptive performance indicates the framework-based disperse strategy has great potential for the construction and application of defect-rich graphene.